Effect of Tai Chi cardiac rehabilitation programme on Quality of Life in Patients with Coronary Heart Disease A Randomized Controlled Clinical Study - Zhang, Jianwei (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details